Proms and Other Racial Ephemera: The Positive Social Construction of African Americans in the “Post”-Civil Rights Era - Rebecca Wanzo (Washington University Journal of Law & Policy, 2010)
During the 2008 Presidential election, one of the key questions was whether the ascendancy of Barack Obama means that we now live in a "post-racial" world. Or, for those who remain skeptical of this claim, what, exactly, does the first African-American presidency mean for race and racial politics? Rebecca Wanzo's Article, Proms and Other Racial Ephemera: The Positive Social Construction of African Americans in the "Post"-Civil Rights Era, tackles this question. Part of the obstacle facing cultural critics and policy analysts alike, Wanzo contends, is that we are most familiar with racism manifest in negative terms—discrimination, violence, and their accompanying discursive trope, negative representations of African Americans. This has left us perplexed by Obama's ascendancy. Yet Wanzo contends that Obama manifests what she calls "positive social construction" of African Americans, which operates by displacing racial "anxieties" onto "safer" objects, thereby disabling material analyses of racist structures and behavior. Assessing events in the public sphere ranging from Don Imus's racial epithets against the Rutgers Scarlet Knights; to segregated proms; to speeches by Eric Holder and Condoleezza Rice; to debates over Obama's health care proposal, Wanzo unpacks the increasing complexity of racial discourse in the United States. Using the psychoanalytic concept of affective displacement, she elegantly demonstrates how positive and negative racial representations operate synthetically to affect public policy discourse, constructing racial progress narratives while disabling empathy for other racially suffering subjects.
Keywords: Civil rights movements; Blacks; Race discrimination; Sociological jurisprudence; African Americans; Displacement (Psychology); Equal protection